Use of special exercises to intensify speed and strength loads in the training of student volleyball teams - Yatskovets A.S. ,; Gabov M.V. ,; Ponimasov O.E. ,; Shelkova L.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to improve the physical and technical training of volleyball players through the use of special speed and strength exercises. Methods and structure of the study. The study tested 25 volleyball players from a student team aged 19.5±0.8 years. Interval training included multiple repetitions of game jump exercises lasting five minutes each at a competitive pace of ball play and relatively short rest periods between sets. Results and conclusions. The use of the repeated interval method of conjugate development of special speed-strength qualities of various muscle groups forms the physiological basis for maintaining a high playing pace and amplitude of performing game techniques by volleyball players in the intense conditions of competitive struggle.